2012
DOI: 10.1148/radiol.11110951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computerized Clinical Decision Support on the Use and Yield of CT Pulmonary Angiography in the Emergency Department

Abstract: Purpose:To determine the effect of evidence-based clinical decision support (CDS) on the use and yield of computed tomographic (CT) pulmonary angiography for acute pulmonary embolism (PE) in the emergency department (ED).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
150
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(165 citation statements)
references
References 23 publications
9
150
5
1
Order By: Relevance
“…Quality improvement projects are needed to encourage physicians to adhere to the current guidelines. A possible method to encourage physicians to adhere to the current guidelines is the use of evidence-based clinical decision support reminders as part of the electronic medical record to remind physicians about the importance of D-dimer assay in the low PCTP group [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Quality improvement projects are needed to encourage physicians to adhere to the current guidelines. A possible method to encourage physicians to adhere to the current guidelines is the use of evidence-based clinical decision support reminders as part of the electronic medical record to remind physicians about the importance of D-dimer assay in the low PCTP group [21]. …”
Section: Resultsmentioning
confidence: 99%
“…After lung cancer diagnosis, Sesen et al demonstrated the use of a Bayesian network decision support system for personalized survival estimates and treatment selection recommendations in lung cancer [8]. While not directly comparable to lung nodule screening, evidence-based clinical decision support tools have also been effective in decreasing the overutilization of CT while increasing yield of the studies performed for CT pulmonary angiography [9].…”
Section: Introductionmentioning
confidence: 99%
“…Quality measurement and feedback programs have become widespread and are often a significant portion of quality improvement efforts. While there is a large and growing body of literature regarding computerized imaging decision support and how it may be used to affect utilization, variation, and appropriateness, [9][10][11][12] there is unfortunately a paucity of research examining the effects of individual physician feedback on test-ordering metrics. While diagnostic imaging use has increased in the absence of demonstrable benefits, 13,14 an understanding of the reasons for this increase and how to change clinicians' behavior is needed.…”
mentioning
confidence: 99%